The Return of Theseus to Athens: A Case Study in Layered Tradition and Reception - Zaccarini, Matteo (Histos, 2015)
The Athenian recovery of Theseus' bones from Scyros is known through a number of literary accounts spanning several centuries. The tradition dates the recovery to the early fifth century and connects it to the Athenian statesman Cimon. Modern reconstructions tend to rely on the combination of different (and possibly conflicting) sources. An analysis of the evidence, however, shows that the story was built up over several centuries, as the various layers of the tradition date to different historical and cultural contexts: its core probably dates to the fourth century. Evidence for any fifth-century element is so scant that most of the story may be safely detached from its alleged historical context.